Matchmaking in Middle Class India - Bhandari, Parul. author. aut Link
XIII, 188 p.
Keywords: This book is an extensive and thorough exploration of the ways in which the middle class in India select their spouse. Using the prism of matchmaking, this book critically unpacks the concept of the 'modern' and traces the importance of moralities and values in the making of middle class identities, by bringing to the fore intersections and dynamics of caste, class, gender, and neoliberalism. The author discusses a range of issues: romantic relationships among youth, use of online technology and of professional services like matrimonial agencies and detective agencies, encounters of love and heartbreak, impact of experiences of pain and humiliation on spouse-selection, and the involvement of family in matchmaking. Based on this comprehensive account, she elucidates how the categories of 'love' and 'arranged' marriages fall short of explaining, in its entirety and essence, the contemporary process of spouse-selection in urban India. Though the ethnographic research has been conducted inIndia, this book is of relevance to social scientists studying matchmaking practices, youth cultures, modernity and the middle class in other societies, particularly in parts of Asia. While being based on thorough scholarship, the book is written in accessible language to appeal to a larger audience.